Relating the formation factor to chloride diffusion in concrete based on low carbon binder types - Achenbach Rebecca; Raupach Michael (MATEC Web of Conferences)
The development and introduction of new types of binders are being driven by the desire to reduce CO2 emissions in cement production. To use these binders as alternatives to Portland cement, their influence on the durability of concrete and reinforced concrete structures must be quantified. The test methods usually focus, for example, on resistance to the penetration of corrosive substances such as chloride through diffusion processes, carbonation resistance or frost resistance. These test methods often involve the use of chemical indicators, the chemical reaction of which can be influenced by the chemical composition of the pore solution contained in the tested concrete or mortar. Therefore, conventional test methods may not be fully applicable for new types of binders. An alternative is to assess the quality of mortars and concretes using electrical methods that are independent of indicator reactions. This article takes a closer look at the electrical resistivity of mortars and concretes and the formation factor as a microstructure parameter. Both, but the formation factor in particular, show great potential for providing meaningful assessments as a parameter for evaluating the durability of mortar and concrete.